ATTITUDE OF DENTAL STUDENTS TOWARDS THEIR ORAL HEALTH CARE. - V.S.S, Charan; N.P, Muralidharan; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Oral health is defined as the oral condition that is free from any kind of disorder which affects the oral cavity and mouth .Generally it is a part of the overall health. Lifestyle and food habit play a important role in ones oral health. Also, there are identified factors that deteriorate the oral health, these include intake of high sugar, carbonated drinks, tobacco and smoking .In India a large number of populations are affected with dental caries and oral cancer. The majority of the factors those are responsible for oral problems are preventable by creating awareness . This study is mainly intended to evaluate the attitude of undergraduate dental students towards their self oral care